Costs and benefits of on-demand HIV preexposure prophylaxis in MSM. (2nd January 2018) - Durand-Zaleski, Isabelle; Mutuon, Pierre; Charreau, Isabelle; Tremblay, Cecile; Rojas, Daniela; Pialoux, Gilles; Chidiac, Christian; Capitant, Catherine; Spire, Bruno; Cotte, Laurent; Chas, Julie; Meyer, Laurence; et al.
Abstract : Objectives: We undertook the economic evaluation of the double-blind randomized ANRS-IPERGAY trial, which showed the efficacy of on-demand preexposure prophylaxis (PrEP) with tenofovir disoproxil fumarate (TDF)-emtricitabine (FTC) in preventing HIV infection among high-risk MSM. Design and methods: The economic evaluation was prospective. Counseling, drugs (TDF-FTC at [Euro sign]500.88 for 30 tablets), tests, visits, and hospital admissions were valued based on in-trial use. The cost of on-demand PrEP/HIV infection averted was compared with the yearly and lifetime costs of HIV infection in France in a cost and benefits analysis. Results: The yearly number of participants needed to treat to prevent one HIV infection was 17.6 (95% confidence interval = 10.7–49.9). The annual cost of counseling was [Euro sign]690/participant. The total 1-year costs of PrEP were [Euro sign]4271/participant, of which [Euro sign]3129 (73%) were drug costs corresponding to 15 tablets of TDF-FTC/month. The yearly cost of on-demand PrEP to avoid one infection was [Euro sign]75 258. Using TDF-FTC generic ([Euro sign]179.9/30 tablets) reduced the 1-year costs of on-demand PrEP to [Euro sign]2271/participant and [Euro sign]39 970/infection averted, respectively. Using TDF-FTC at international market discounted prices ([Euro sign]60/30 tablets) reduced the costs to [Euro sign]1517/participant and the cost to [Euro sign]26 787/infection averted, comparable with the yearly treatment cost of HIV infection in France. On-demand PrEP was found to be cost saving in France if the duration of exposure was less than 7.5 years at current drug price and 13 years at generic price. Conclusion: On-demand PrEP in high-risk MSM with TDF-FTC can be considered cost saving. Other benefits include the treatments of other diseases and reductions in secondary infections.